(untitled) - Fogle, Bruce (London, 2007)
The book covers over 420 dog breeds and varieties, describes their history and shows the way to look after a dog successfully. It also includes over 600 glorious photographs that capture the character of selected breeds in an outdoor setting
Keywords: Dogs,Dog breeds,Chó,Các loài chó; encyclopedias,Encyclopedias.,Bách khoa toàn thư,Bách khoa toàn thư